ANALISIS HUKUM PEMBATALAN PUTUSAN ARBITRASE NASIONAL TERHADAP KEPERCAYAAN PELAKU USAHA - Miftachul Jannah; Rihantoro Bayuaji (Fakultas Ilmu Sosial dan Humaniora, 2025)
This study aims to analyze the legal basis, practices of annulment of national arbitration awards, and their impact on business confidence. Arbitration as regulated under Law No. 30 of 1999, is designed to serve as an efficient and final dispute resolution mechanism. However, the annulment of arbitration awards by courts based on Article 70 of the Arbitration Law often leads to legal uncertainty, reduces efficiency, and undermines business confidence. The study finds that weaknesses in regulations, overlapping authorities, and inconsistencies in court decisions are the main causes of these issues, which negatively affect investment and Indonesia's attractiveness as an arbitration forum. As a solution, the study recommends strengthening arbitration regulations, limiting judicial authority, and enhancing the professionalism of arbitrators to ensure legal certainty and uphold the integrity of the arbitration mechanism in Indonesia.